Scientific Immortalism and the Problematic Future of Technocentric Immortality - Odorcak, Juraj (Journal for the study of religions and ideologies, 2020)
Scientific immortalism is an ideology that argues in favor of technologically facilitated immortality. According to proponents of scientific immortalism immortality will be achieved through the future technological realizations of prospective advances in knowledge of medical, biological, informational and material sciences. Supporters of scientific immortalism therefore usually believe that biotechnological modification and enhancement of humans is the most authentic, secure and safe way towards the ideal of immortal beings. This indicates that in scientific immortalism science is mostly seen as an innovative and sophisticated tool for acquiring some of the classical goals of religion. The long historical discourse of religion and philosophy, however, shows that immortality isn't a uniform concept and faith in immortality may come in many different forms. Justification of goodness of technocentric immortality therefore crucially depends on the precise specification of the right kind of immortality. The article deals with the characterization of different forms of immortality, which are relevant to the current debate about the predictions of scientific immortalism. It is argued, that some forms of technocentric immortality could lead to the loss of beneficial human values and toward the destruction of usual features of personal identity. Scientific immortalism should, therefore, stay scientific and accept that the superstitious idealization of science doesn't miraculously imply, that the future of technologically mediated immortality will be necessary always good.